Sekretesskydd inom Luleå kommuns Socialförvaltning vid informationsutbyte med andra myndigheter - Berglund, Tomas (2011)
It is important that confidential information divisions within Luleå Municipality exchange with other divisions do not become available to unauthorized persons, since both individuals and the municipality itself may be damaged by it. With this in mind, the municipality plans to install an encryption system that will help to protect confidential information. The purpose of this thesis was to evaluate the procedures and technical means the personnel at the Social Services have to work with in order to protect confidential information. The questions to be answered are: How is the information protected from unauthorized access? What are the legal requirements for the protection? How well are the procedures adapted? How should the implementation of the system be in order to make it useable? The results showed that the informants had good knowledge about how confidential information has to be protected from unauthorized access. However, not all informants had rules and procedures about how they should work in order to protect confidential information in certain situations. For some of the informants the rules sometimes were perceived as ridiculous, which made the informants less willing to follow them. On the whole, however, the rules and procedures were considered to be well adapted by the informants. A new encryption system would nevertheless probably simplify and make the work more efficient. Validerat; 20111009 (anonymous)